Verification of the usefulness of short increment sensitivity index (SISI) test in determining bone conduction thresholds - Narendiran K (Journal of All India Institute of Speech and Hearing, 1970)
Swisher, Stephens and Doehring (1966) suggested that the SISI test might be interpreted as an indirect measure of bone conduction thresholds. Swisher et al (1966) also showed that normal and non-adapting sensorineural impaired ears discriminated a signal of 1 dB or less equally well at equivalent SPL. The study by Young and Harbert (1967) showed that at SPL's of 45 and above every normal subject showed a SISI score of 65 per cent or higher for all frequencies. In general, a high SISI score occurs when at least 60 dB SPLreaches the inner ear. Sound pressure level (SPL) reaching the inner ear is the determining factor in the perception of 1 dB increments (Young and Harbert, 1967; Harbert, Young and Weiss, 1969; Martin and Salas, 1970).